ON MONETARY COMPENSATION FOR NON-PECUNIARY DAMAGE TO LEGAL ENTITIES IN SERBIAN LAW - APPENDIX TO THE REFORM OF DAMAGES LAW - Savčić, Sanja Milan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The right to monetary compensation for non-property damage is not enjoyed in the same way by all legal entities, i.e. legal entities and natural persons. In theory and practice, there are different approaches regarding the issue of whether a legal entity can suffer non-material damage of the same intensity and in the same form as is the case with natural persons. In this regard, it was pointed out that a legal entity can have a reputation, and therefore a damaged reputation can be the basis for an obligation to pay compensation for the damage suffered as a result. The discussion on the merits of monetary compensation for non-material damage to legal entities continued until the adoption of the legal understanding of the Civil Department of the Supreme Court of Serbia on February 5, 2001. The more recent theory of obligation law discusses this issue in the context of the need to review the current rules of tort law. In this sense, it is emphasized that the objective concept of non-property damage, which excludes physical or psychological pain and fear from the conceptual definition, provides a legal basis for monetary compensation of such damage to legal entities. Such changes have already been implemented in some countries of the former Yugoslavia. When it comes to Serbia, theory and practice are still waiting for reform, although there are indications that reform has already taken place on the normative level. Therefore, the aim of this paper is to answer the question whether in our law there is a right of a legal entity to compensation for non-property damage.
Keywords: non-pecuniary damage, legal entity, business reputation, objective conception, subjective conception.